A study on 3D/BIM-based on-site performance measurement system for building construction - Cha, Hee Sung; Kim, Jun (Journal of Asian Architecture and Building Engineering, 2020)
Performance measurement has become conventional in construction management. However, it is non-trivial to establish an effective system to capture, evaluate, and feedback the on-site data. Whilst 3D object–based technology prevails in the industry, project managers remain accustomed to text-based system. Unstructured data format requires a tremendous amount of time and effort when analyzing a project in detail. To overcome this issue, an extensive literature review in conjunction with industry feedback has been conducted. Based on this preliminary investigation, the authors have proposed an on-site performance measurement system that interlinks 3D object with a spreadsheet. The system enables project managers to recognize the performance and/or productivity of a project in real time and helps find timely remedies in updating the original plan. One of the key findings includes that the identified eight on-site productivity factors should be embedded into a 3D model in effectively measuring the performance for a particular project. The new system also provides a useful tool in managing the productivity of a project. The main contribution of this study is the proposition and verification of a novel methodology that effectively manages on-site performance information by relating 3D objects with productivity factors in building construction.
Keywords: Building construction; Construction management; Effective systems; Literature reviews; On-site performance; Performance measurements; Productivity factors; Text-based systems; 3D/BIM; information technology; on-site information; performance measurement; productivity factor